Om Grundtvigs sanges liv i Nordamerika - Stølen, Marianne (Grundtvig-Studier, 2008)
Om Grundtvigs sanges liv i Nordamerika [On the life of Grundtvig’s songs in North America] By Marianne Stølen The article discusses three important conditions for that rich life which Grundtvig’s songs have enjoyed among Danish-Americans in North America. Treated first is the songbook of Frederik Lange Grundtvig, Sangbog for det danske Folk i Amerika [Songbook for the Danish folk in America] (1888), commonly known as “the red one,” with focus upon F. L. Grundtvig’s selection of familiar and unfamiliar songs and hymns gathered from his father’s treasury of song and his reworking of some of these with regard to their relevance for use among the Danish immigrants. Next is described the production of songs among the migrants, especially the Danish pastors, with examples of the word-choice which reveals an assimilation of key conceptwords from Grundtvig’s writings along with readily recognisable echoes of lines from the Grundtvig classics. There follows a description of the Hymnal for Church and Home (1927) and the Danish-American A World of Song (1941), each of which in its way collaborated in building a bridge between successive generations of users. Particular attention is drawn to the translations contributed to the songbook by the Danish-American translator and pastor S. D. Rodholm, with use of examples from Grundtvig’s authorship. Finally a glimpse is offered into the role played today by Grundtvig’s songs in the song-repertoire of Danish-American conventions and among the present members of two singing groups in the Pacific Northwest.